2022
DOI: 10.1177/21582440211069385
|View full text |Cite
|
Sign up to set email alerts
|

Understanding National Identity Construction in China-ASEAN Business Discourse

Abstract: Few studies have investigated national identity construction in a diachronic and holistic manner. To address this gap, in applying constructivist views of international relations and Critical Discourse Analysis (CDA), this paper analyzes business news titles of Chinese and ASEAN (Association of South-East Asian Nations) country mainstream media to reveal identities that both parties construct of one another and relationships between discourse and identity construction. Findings suggest that ASEAN identities co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…When researching the construction of image discourse, some scholars utilize analyzing tools and approaches such as the discourse-semantic systems in Systemic Functional Linguistics (SFL) theory, the discourse-historical approach in (CDA), and conceptual metaphors theory, combined with in-depth interviews and small focus groups, to investigate how China's national image and identity is discursively constructed and promoted externally to an international audience (Shao, 2017;Liu and Chang, 2021;Ban and Pan, 2020;Yuan et al, 2022;Zhang, 2022). To gain a comprehensive and diachronic understanding of China's national image, scholars (Kim, 2014;Zhang and Wu, 2017;Yuan et al, 2022;Zhang, 2022) often employ a corpus-based CDA approach to identify universal and frequent characteristics of China's image across the entire corpus by examining collocational and other recurrent patterns associated with specific lexical items. Meanwhile, a critical discourse analysis-informed approach is deemed most suitable for scrutinizing specific stretches of text to locate the typical and recurrent linguistic patterns in the context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When researching the construction of image discourse, some scholars utilize analyzing tools and approaches such as the discourse-semantic systems in Systemic Functional Linguistics (SFL) theory, the discourse-historical approach in (CDA), and conceptual metaphors theory, combined with in-depth interviews and small focus groups, to investigate how China's national image and identity is discursively constructed and promoted externally to an international audience (Shao, 2017;Liu and Chang, 2021;Ban and Pan, 2020;Yuan et al, 2022;Zhang, 2022). To gain a comprehensive and diachronic understanding of China's national image, scholars (Kim, 2014;Zhang and Wu, 2017;Yuan et al, 2022;Zhang, 2022) often employ a corpus-based CDA approach to identify universal and frequent characteristics of China's image across the entire corpus by examining collocational and other recurrent patterns associated with specific lexical items. Meanwhile, a critical discourse analysis-informed approach is deemed most suitable for scrutinizing specific stretches of text to locate the typical and recurrent linguistic patterns in the context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cultural identity is an individual’s recognition of a group’s attitudes, feelings, degree of belonging ( Berry et al, 1989 ), ideals and values ( Schwartz et al, 2006 ), and other social identities such as class, nationality and race, which is of enormous importance to a culture’s unity, consensus and self-confidence ( Villarroya, 2012 ; Över, 2016 ; C. Zhang et al, 2019 ; Zhang et al, 2021 ; Azada-Palacios, 2022 ). It is the foundation of cultural self-confidence, national stability and unity for a country to enhance its cultural identity ( Schwartz et al, 2006 ; Li et al, 2015 ; Waechter, 2015 ; Yuan et al, 2022 ). However, numerous studies have shown that it is not easy to construct cultural identity ( Minnaert, 2014 ; Van Der Zwet, 2016 ; Grajzl et al, 2018 ; Chitima, 2022 ).…”
Section: Introductionmentioning
confidence: 99%